Emotional Information in News Reporting on Audience Cognitive Processing in the Age of Posttruth: An Electroencephalogram and Functional Connectivity Approach - Yang, Ya; Xiu, Lichao; Yu, Guoming (Frontiers in Psychology, 2021)
The purpose of the present study is to explore how the emotionalized expression of news content in the post-truth era affects the audiences’ cognitive processing. One news text written with two different expression types (emotional expression vs. neutral expression) was adopted as experiment materials in the study, and changes in cortical activity during news reporting reading tasks were examined with electroencephalograms (EEGs) sampled from nine sites and four channels, and analyzed with weighted phase lag index (wPLI) based on brain functional connectivity (FC) method. The results show that emotional discourses caused a stronger cortical brain activity and more robust brain functional connectivity (beta oscillations); besides, reading emotionalized expression consumed more attention resources but fewer cognitive resources, which may impede the audiences’ further rational thinking.